A tributação sobre os serviços na nuvem - Haendchen, Hans Bragtner (2018)
The present work will expose a highly relevant topic at current time, the cloud service, an extremely intriguing theme in legal tax discussions, object of several debates by the exponential change of paradigms. It started with the knowledge of these tools to later learn about their legal nature, protection and form of economic exploitation. Entering juridical field, the constitutional principles of taxation dealing with federation, legal certainty and tax legality (tax typicity) were explored, since they are relevant to the debate about tax jurisdiction, legal limits and archetypes of taxes, such as the definition of concepts or types by the original constituent. Thus, the concept of service and merchandise was approached in Federal Constitution of 1988, as well as the position of the doctrine and the Federal Supreme Court, examining the cases of greater repercussion. Finally, it analyzed the conflict of jurisdiction between States and Municipalities for the taxation of Software as a Service (SaaS)